PENGARUH KEBIJAKAN PERUSAHAAN TERHADAP ETOS KERJA KARYAWAN DENGAN KOMPENSASI SEBAGAI VARIABEL INTERVENING (Studi Kasus Karyawan KAP Drs. Chandra Dwiyanto di Surabaya) - Nuraini, Fitri (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2018)
The existence of the theory of compensation from Dessler in the concept of factors that affect compensation are 3 factors: internal organization, personal employees and external companies. In this case the internal factor of the organization which includes the funds of the organization and the union, the union is an example of one company policy that can affect employee work ethic. If the company's policy of overtime, salary increases and holiday allowances (THR) in accordance with the provisions of the Workers Act, indirectly can improve employee performance spirit. Based on the compensation theory, this study tries to test the indirect relationship between company policy and employee work ethic by entering the compensation variable as intervening variable. The population of this research is all employees of Public Accountant Firm Chandra, amounting to 41 people. This research uses quantitative research method with Path Analysis analysis technique whose test is done with software SPSS 13.0 The result of the analysis concludes that compensation as intervening variable mediates to the influence of company policy on employee work ethic. Based on these results, the hypothesis of this study is evident